Advances in clinical applications of microneedle - Chen, Kequan; Sun, Xinyu; Liu, Yangkaiyuan; Li, Shiyu; Meng, Dianhuai (Frontiers in Pharmacology, 2025)
Microneedle (MN) technology, characterized by its micron-scale structure, can effectively break through the skin barrier, enhance the efficiency of transdermal drug delivery and achieve precise biosignal detection. Research indicates that MNs demonstrate superior safety and efficacy in clinical applications, significantly improving drug delivery efficiency, enhancing patient compliance and reducing side effects. In the field of biosensing, the combination of MN arrays and biosensors enables highly sensitive real-time monitoring of biomarkers. In cancer treatment, MNs exhibit potential for targeted drug delivery, gene therapy, and immunostimulation. Moreover, MNs present broad prospects in wound healing, scar repair, anti-aging and skin disease treatment. This review aims to systematically summarize recent advances in MNs applications across transdermal drug delivery, biosensing, cancer therapy, and skin disease repair through recent high-quality studies, and to explore future development prospects.